2015
DOI: 10.1103/physrevb.92.134524
|View full text |Cite
|
Sign up to set email alerts
|

Electron scattering, charge order, and pseudogap physics inLa1.6xNd0.4SrxCuO4: An angle-resolved photoemission spectroscopy s

Abstract: We report an angle-resolved photoemission study of the charge stripe ordered La1.6−xNd0.4SrxCuO4 system.A comparative and quantitative line shape analysis is presented as the system evolves from the overdoped regime into the charge ordered phase. On the overdoped side (x = 0.20), a normal state anti-nodal spectral gap opens upon cooling below 80 K. In this process spectral weight is preserved but redistributed to larger energies. A correlation between this spectral gap and electron scattering is found. A diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 106 publications
(163 reference statements)
21
60
0
Order By: Relevance
“…At p = 0.24, Matt et al observe no gap at all, confirming that the pseudogap phase begins below p = 0.24 [29]. Again, this is perfectly consistent with transport data (Fig.…”
Section: A Pseudogap In Arpes and Transportsupporting
confidence: 81%
See 4 more Smart Citations
“…At p = 0.24, Matt et al observe no gap at all, confirming that the pseudogap phase begins below p = 0.24 [29]. Again, this is perfectly consistent with transport data (Fig.…”
Section: A Pseudogap In Arpes and Transportsupporting
confidence: 81%
“…Recently, Matt et al reported ARPES measurements on Nd-LSCO that confirm this interpretation [29]. They observe a partial anti-nodal gap at p = 0.20, in the normal state just above T c .…”
Section: A Pseudogap In Arpes and Transportsupporting
confidence: 60%
See 3 more Smart Citations